Design and develop modular CNC machine : machine based part - Muhamad Faiq Fida'ie, Azami (2017)
Modular machine design is a design approach that subdivides a system into smaller part called module or section in order to respond from rapid changes of the design which also effect on how difficult the machine construction can be assemble and dissemble. This thesis presents the design and the develop of modular CNC machine and the priority is on how the modularity can apply on the design. The modular CNC machine is in a small scale which it can operate like normal CNC machine but has smaller limited area of machining also limited type of material that it can machine such as soft aluminum and plastic. The design was sketch using Catia V5 software then analyze the design also using Catia V5 software to determine how maximum the machine structure can withstand the external force. The development of the machine structure begins when the result of analysis approves the design. The machine is developed by following the modular design which is the machine is divide into two sections. First section is Y - axis part and the second section is X- axis and Z - axis part. Both section successfully can be assembled and dissemble easily because of its modularity design.